Going lean how the best companies apply lean manufacturing principles to shatter uncertainty, drive innovation, and maximize profits - Ruffa, Stephen A., 1961- (American Management Association, 2008)
Follow the lead of Toyota, Southwest Airlines, and Wal-Mart and embrace "Lean Dynamics" for business success.
Keywords: Business logistics -- Management.; Production management.; Manufacturing processes.; Organizational change.; elektronické knihy; electronic books